IPTEKS PENGHITUNGAN TINGKAT PENGEMBALIAN YANG DIHARAPKAN ATAS SAHAM BIASA - Pontoh, Winston (Universitas Sam Ratulangi, 2017)
Most of investors normally expect optimum return for their investments especially for stock investment, In objective to get optimum return then the investors should know how much the required rate of return for each stock that they want to invest. As the applied science, this study shows that Capital Asset Pricing Model can estimate the required rate of return for investors as the information for them to take investment decision. This study uses one public firm listed in Indonesia Stock Exchange in period of 2015 as the sample to estimate its required rate of return. This study shows that the risk free rate, market return, and stock beta are the main keys for estimating the required rate of return in application of Capital Asset Pricing Model.